Are we eating the world's megafauna to extinction?. Issue 3 (6th February 2019) - Ripple, William J.; Wolf, Christopher; Newsome, Thomas M.; Betts, Matthew G.; Ceballos, Gerardo; Courchamp, Franck; Hayward, Matt W.; Van Valkenburgh, Blaire; Wallach, Arian D.; Worm, Boris
Abstract: Many of the world's vertebrates have experienced large population and geographic range declines due to anthropogenic threats that put them at risk of extinction. The largest vertebrates, defined as megafauna, are especially vulnerable. We analyzed how human activities are impacting the conservation status of megafauna within six classes: mammals, ray‐finned fish, cartilaginous fish, amphibians, birds, and reptiles. We identified a total of 362 extant megafauna species. We found that 70% of megafauna species with sufficient information are decreasing and 59% are threatened with extinction. Surprisingly, direct harvesting of megafauna for human consumption of meat or body parts is the largest individual threat to each of the classes examined, and a threat for 98% (159/162) of threatened species with threat data available. Therefore, minimizing the direct killing of the world's largest vertebrates is a priority conservation strategy that might save many of these iconic species and the functions and services they provide.